Evaluation of in situ stress changes with gas depletion of coalbed methane reservoirs. Issue 8 (15th August 2014) - Liu, Shimin; Harpalani, Satya
Abstract A sound knowledge of the stress path for coalbed methane (CBM) reservoirs is critical for a variety of applications, including dynamic formation stability evaluation, long‐term gas production management, and carbon sequestration in coals. Although this problem has been extensively studied for traditional oil and gas reservoirs, it is somewhat unclear for CBM reservoirs. The difference between the stress paths followed in the two reservoir types is expected to be significant given the unique sorption‐induced deformation phenomenon associated with gas production from coal. This results in an additional reservoir volumetric strain, which induces a rather "abnormal" loss of horizontal stress with depletion, leading to continuous changes in the subsurface formation stresses, both effective as well as total. It is suspected that stress changes within the reservoir triggers formation failure after significant depletion. This paper describes an experimental study, carried out to measure the horizontal stress under in situ depletion conditions. The results show that the horizontal stress decreases linearly with depletion under in situ conditions. The dynamic stress evolution is theoretically analyzed, based on modified poroelasticity associated with sorption‐induced strain effect. Additionally, the failure tendency of the reservoir under in situ conditions is analyzed using the traditional Mohr‐Coulomb failure criterion. The results indicate that depletion may lead to coal failure, particularly in deeper coalbeds and ones exhibiting large matrix shrinkage.